Effects of Separation and Purification on the Structure and Lipid-lowering Activity in Vitro of Tremella fuciformis Polysaccharide - Yihan WANG; Qingyun XIE; Jianwen TENG; Li HUANG; Ning XIA (Shipin gongye ke-ji, 2025)
In this study, Tremella fuciformis crude polysaccharide (TFP) was extracted using hot water extraction and refined to yield TFP-1 using a DEAE-52 cellulose column. This study evaluated the pure and unpurified polysaccharides' composition, structure, and in vitro hypolipidemic action. The total sugar content of TFP-1 grew to 78.19%, the uronic acid content increased to 31.39%, and the viscosity reduced to 108.33 mPa·s in comparison to TFP, according to the data. TFP had more linear macromolecules and a broader variety of molecular weights. Before and after purification, the composition of monosaccharides did not change, but the molar ratio did. Mannose, xylose, fucose, glucuronic acid, glucose, galactose, and glucosamine hydrochloride made up the monosaccharide composition of TFP and TFP-1. Their molar ratios were 0.51:0.212:0.182:0.076:0.013:0.006:0.001 and 0.552:0.193:0.132:0.103:0.014:0.004:0.003. Furthermore, the smooth, flat microscopic structure of the refined polysaccharides gave way to a rough, fibrous structure. The results of in vitro lipid-lowering tests demonstrated that TFP had a considerably greater cholesterol binding rate (32.64%) at 10 mg/mL and pancreatic lipase inhibition rate (61.51%) at 15 mg/mL compared to TFP-1 (P<0.05). At 10 mg/mL, TFP-1's bile acid binding rate was 27.43%, substantially greater than TFP's (P<0.05). This suggested that Tremella fuciformis polysaccharide's separation and purification altered some of its structural characteristics, which in turn had an impact on its hypolipidemic action. The findings offered a theoretical foundation for the creation of foods related to Tremella fuciformis polysaccharide that had the ability to decrease cholesterol.